'The Saviors Are Also Humans': Understanding the Role of Quality of Work Life on Job Burnout and Job Satisfaction Relationship of Indian Doctors. (June 2019) - Srivastava, Shalini; Misra, Richa; Madan, Poornima
The purpose of this study is to explore the mediating role of Quality of Work Life on Job Burnout and Job Satisfaction relationship. The present research constituted of 240 doctors belonging to 4 different states of India who were working in either in medical colleges, private hospitals or had their own private clinics. The data was assessed through statistical techniques like correlation, reliability and mediator regression analysis. The study results revealed that there is a significant and negative association between job burnout and job satisfaction, a significant and positive association between QWL and Job Satisfaction and a significant and negative relationship between Job Burnout and QWL. Doctors devote their lives to the practice of medicine, work sincerely in their pursuit to provide best care for patients. Hospital administration needs to encounter various imperative job demands that predict burnout by designing diverse interventions as all job demands cannot be condensed, also burnout can't be entirely eradicated from the work place of doctors.